Obtenção dos parâmetros do plano oclusal com métodos de visão computacional - Vianna, Filipi Damasceno (2012)
The occlusal plane is an imaginary plane that passes between the upper and lower dental arches and is used as reference for assessments in several kinds of dental treatment. The correct orientation of this plan is important for a successful treatment because it is from this orientation, for example, that a surgery can be planned. The treatment planning is often done, using virtual or physical models (plaster) to replicate the dental arches and the patient's teeth. This replication, however, reach the problem of how to register the patient´s occlusal plane orientation and transport it to the model. Motivated by this problem this paper has developed a process to obtain both an anthropometric reference, as the angles relating the occlusal plane to this reference. The process presented in this work is based on the application of computer vision techniques on two images of the patient's head, one from the front and another from the profile. It also presents a method to transport this information to a plaster model and virtual